Pectin's influence on the forming of the butter structure - Rashevska, Tamara (My University, 1998)
We have investigated the possibility of pectin usage for the stabilization of the butter and dessert butterlike pastes with the low content of the fat.
Keywords: butter; pectin; butter structure; пектин; вершкове масло; структура вершкового масла; кафедра технології молока і молочних продуктів